Contesting #IslamNusantara on Instagram: A Shared Interest Pool - Rohmatulloh, Dawam Multazamy; Marwantika, Asna Istya (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
As one of the demanding discourses of Indonesian Islam, Islam Nusantara has made a further round of Indonesian Muslim polarisation among the proponents on the one side and the opponents on another, let alone in the digital era nowadays. For the Muslim communities, new media are not only used for communication activities but also to assist the da'wa (proselytisation) and its contestation. This paper, thus, aims to portray activities of social media users, particularly Instagram, using the #IslamNusantara hashtag to convey their ideas. This paper seeks to explore the motives of how the Instagram users do involve in the contestation of #IslamNusantara and to what extent they publish their argument to support, criticise, or even refuse the concept of Islam Nusantara. The method used in this article is netnography, analysing a total of 344,000 hashtags #IslamNusantara on Instagram. Finally, this paper anticipates a yet-to-end online contestation among the Muslim communities within a new interest pool: #IslamNusantara.